The Foe You Know: Observations of Interspecific Interactions Between Small Cetaceans and Northern Resident Killer Whales (Orcinus orca) in the Northeast Pacific - Brittany C. Visona‐Kelly; Lance G. Barrett‐Lennard (Ecology and Evolution, 2025)
ABSTRACT We documented the first aerial observations of interspecific interactions of fish‐eating, northern resident killer whales (Orcinus orca) with two small cetacean species, Dall's porpoises (Phocoenoides dalli) and Pacific white‐sided dolphins (Lagenorhynchus obliquidens), off northeastern Vancouver Island, BC, Canada. Specifically, we used drone‐collected data to compare observations of porpoises and dolphins interacting with northern resident killer whales to understand factors which may promote interspecific interactions. From 2018 to 2021, 42 interactions were opportunistically recorded of Dall's porpoises (19%), Pacific white‐sided dolphins (74%), and both species (7%) approaching groups of traveling, milling, socializing, and resting northern resident killer whales. The mean group size of killer whales during interactions with dolphins (an average of 8 killer whales) and porpoises (an average of 3 killer whales) was significantly different. Porpoises interacted only with small groups (n ≤ 5) of killer whales, while dolphins interacted with larger groups (n ≥ 25). This suggests that the likelihood of interaction by each species is influenced by killer whale group size. However, the age and sex composition of killer whale groups, as well as the number of small cetaceans present, were found to have no significant effect on interaction patterns. Additionally, we never observed killer whales initiating interactions. We discuss several adaptive benefits, including antipredator, foraging, hydrodynamic, and social advantages, to dolphins and porpoises that may drive the observed interactions. The benefits of interactions appeared to be predominantly antipredator‐focused and species‐specific, with both species possibly also benefiting from increased hydrodynamic efficiency while swimming. While opportunistic, our observations provide detailed accounts of non‐predatory interactions between small cetacean species and northern resident killer whales. Future studies focusing on the drivers of mixed‐species group formation in the North Pacific are needed, and we suggest that these utilize drones as a platform for data collection.